The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/859213
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Color Doppler Ultrasonography for Esophagogastric Varices

Abstract: Esophagogastric varices are considered to be the most common complication in patients with portal hypertension. Endoscopic ultrasonography not only visualizes the surface of the varices but also provides detailed information about their internal structure. The direction of blood flow can be determined and its velocity measured only via endoscopic color Doppler ultrasonography (ECDUS). This can show graphically esophageal varices, paraesophageal veins, and passageways in esophageal variceal patients and gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Para-ECVs have also been studied, and a histopathological causal relationship has been demonstrated by the existence of both peri-, and para-ECVs [27]. Furthermore, these ECVs often communicate with esophageal varices via PV, and such relationships can be observed in detail on EUS [14,15,24,27] (Figure 5c). According to studies of the blood flow direction of the PV using color Doppler EUS, it was found that most PV in the lower esophagus served as inflow pathways [14,15].…”
Section: Evaluation Of the Hemodynamics Of Esophageal Variesmentioning
confidence: 96%
See 1 more Smart Citation
“…Para-ECVs have also been studied, and a histopathological causal relationship has been demonstrated by the existence of both peri-, and para-ECVs [27]. Furthermore, these ECVs often communicate with esophageal varices via PV, and such relationships can be observed in detail on EUS [14,15,24,27] (Figure 5c). According to studies of the blood flow direction of the PV using color Doppler EUS, it was found that most PV in the lower esophagus served as inflow pathways [14,15].…”
Section: Evaluation Of the Hemodynamics Of Esophageal Variesmentioning
confidence: 96%
“…When performing electronic radial-arrayed EUS, it is difficult to achieve detailed esophageal intramural and extramural evaluation, which is possible with UMP. However, the color Doppler function enables identification of the direction of the blood flow of perforating veins communicating between the esophageal varices and extramural blood vessels, and it also aids in understanding the hemodynamics surrounding the esophageal varices in greater detail [14,15] (Figure 3). Perforating veins with blood flow into esophageal varices may remain after treatment and contribute to recurrence, which suggests the importance of eliminating these at the time of treatment.…”
Section: Eus Procedures For the Diagnosis Of Esophageal Varicesmentioning
confidence: 99%
“…In order to identify factors that contributed to recurrence of varices and bleeding after endoscopic treatment some authors have also used color Doppler EUS. The association of Doppler to ultrasound images obtained by EUS allows both the visualization of varices and its collaterals and the understanding of the hemodynamics of the portal venous system and even the effects of endoscopic and pharmacological therapeutics for esophageal varices[ 41 ]. In a study by Hino et al[ 42 ] the color Doppler EUS was used to study the hemodynamics changes and morphology pattern of the left gastric vein (the main feeder vessel of esophageal varices).…”
Section: Eus and Endoscopic Therapy Of Gastroesophageal Varicesmentioning
confidence: 99%
“…The endoscopic diagnosis of high risk for bleeding of gastric varices is not always easy to assess, and sometimes they are mistaken for large gastric folds or submucosal tumors. The magnetic resonance and CT allow the visualization of the entire portal venous system, however the accuracy of these techniques in distinguishing between submucosal gastric varices and perigastric collateral veins remains limited[ 41 ].…”
Section: Eus and Endoscopic Therapy Of Gastroesophageal Varicesmentioning
confidence: 99%
“…Although endoscopic findings are typically evaluated with the naked eye, this approach cannot be used to assess deep collateral vessels to identify the RCS. Therefore, endoscopic ultrasonography, which was developed to evaluate diseases of the mediastinum, is used to visualize the collateral channels that surround the distal esophagus and upper stomach[ 3 - 10 ], and may enhance variceal detection and improve therapeutic targeting[ 11 - 20 ]. Endoscopic variceal ligation (EVL) and endoscopic injection sclerotherapy (EIS) are the two major techniques used in endoscopic EV therapy[ 21 ].…”
Section: Introductionmentioning
confidence: 99%